2010
DOI: 10.1213/ane.0b013e3181c22021
|View full text |Cite
|
Sign up to set email alerts
|

Pressures Available for Transtracheal Jet Ventilation from Anesthesia Machines and Wall-Mounted Oxygen Flowmeters

Abstract: Oxygen sources other than dedicated jet ventilator connectors to high-pressure pipeline oxygen may supply adequate working pressure, but each type of oxygen source needs testing to ensure that it supplies adequate working pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Another method of oxygen delivery in cannula cricothyroidotomy is a direct connection between the cannula and tube from another oxygen supply. Fassl et al investigated the driving pressure of sources of oxygen, such as wall-mounted oxygen flowmeters and AM auxiliary oxygen flowmeters [ 18 ]. The oxygen flush mechanisms of several kinds of AMs were found to be unable to deliver sufficient flows, as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method of oxygen delivery in cannula cricothyroidotomy is a direct connection between the cannula and tube from another oxygen supply. Fassl et al investigated the driving pressure of sources of oxygen, such as wall-mounted oxygen flowmeters and AM auxiliary oxygen flowmeters [ 18 ]. The oxygen flush mechanisms of several kinds of AMs were found to be unable to deliver sufficient flows, as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen flush mechanisms of several kinds of AMs were found to be unable to deliver sufficient flows, as seen in the present study. They concluded that several flowmeters were acceptable to use as oxygen sources for TTJV in their study [ 18 ], but these methods needed specialized devices to connect the catheter for TTJV.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the older Dahtex-Ohmeda Aestiva/5 (GE Healthcare, USA) and Dahtex-Ohmeda Anesthesia Delivery Unit, fresh gas decoupling was done through mechanisms that required several breaths to equilibrate, and thus did not immediately protect against sudden increases in flow and pressure during inspiration. 4 As such, it would be dangerous to assume that the oxygen flush valve can always be safely used during inspiration in all machines with fresh gas decoupling in young children.…”
Section: Correspondencementioning
confidence: 99%
“…The oxygen flush valve has also been described for use in jet ventilation should other oxygen sources not be available. 3,4 All modern anesthesia machines provide easy access to an oxygen flush valve because there may be instances in which rapid oxygen delivery is needed.…”
mentioning
confidence: 99%
“…The oxygen flush valve has also been described for use in jet ventilation should other oxygen sources not be available. 3,4 All modern anesthesia machines provide easy access to an oxygen flush valve because there may be instances in which rapid oxygen delivery is needed.…”
mentioning
confidence: 99%